Does one size fit all in the Euro Area? Some counterfactual evidence - Sergio Destefanis; Matteo Fragetta; Emanuel Gasteiger (Vienna University of Technology, Institute of Statistics and Mathematical Methods in Economics, Research Group Economics, 2021)
This paper examines whether Euro Area countries would have faced a more favorable inflation output variability tradeoff without the Euro. We provide evidence supporting this claim for the periods of the Great Recession and the Sovereign Debt Crisis. The deterioration of the tradeoff becomes insignificant only after Draghi's 'whatever it takes' announcement. Results show that the detrimental effect of the Euro is more severe for peripheral countries. We base our results on a novel empirical strategy that, consistently with monetary theory, models the joint determination of the variability of inflation and output conditional on structural supply and demand shocks.
Keywords: C32; E50; F45; 330; Euro Area; Monetary Policy; Difference-in-Differences